PENGEMBANGAN KAWASAN AGROPOLITAN - Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2012)
Abstract: This research aims to define the location that meets the requirements of the nationaland regional support agropolitan, and make a plan for the development of agropolitan. Imogiriis a district that has potential in agriculture, animal husbandry, farming, forestry, and aquaculture. But the development of the present day have led to a gap between urban and rural areas and urban bias. This condition is indicated by the relatively high level of urbanization and the impact on the agricultural sector. Therefore we need an alternative strategy for rural development, one of which is through the development agropolitan. In the division of Strategic Development Kasawan Agropolitan (KSA) Imogiri sub divided into 4 KSA. KSA is a functionof institutional develop farmer businesses on/off farm an effective, efficient, and competitive. Abstrak: Penelitian ini bertujuan menentukan lokasi yang memenuhi persyaratan nasional dan regional yang mendukung agropolitan, dan membuat rencana untuk pengembangan agropolitan. Imogiri adalah kabupaten yang memiliki potensi di bidang pertanian, peternakan, pertanian, kehutanan, dan perikanan. Tetapi perkembangan hari ini telah menyebabkan kesenjangan antara daerah perkotaan dan pedesaan dan bias perkotaan. Kondisi ini ditunjukkan dengan tingkat urbanisasi yang relatif tinggi urbanisasi dan dampak pada sektor pertanian. Oleh karena itu diperlukan strategi alternatif untuk pembangunan pedesaan, salah satunya adalah melalui pengembangan agropolitan. KSA adalah fungsi dari kelembagaan yang mengembangkan usahatani on / off farm yang efektif, efisien, dan kompetitif.